The model of the oil and gas system of the Devonian sedimentary complex of the Biloliskyy block of the Dobrudja foredeep - Hnidets, Volodymyr; Hryhorchuk, Kostyantyn; Koshil, Lesia; Yakovenko, Myroslava (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
The purpose of the article is to find out the main principal features of the ontogenesis of the oil and gas system of the Devonian deposits of the Dobrudja Foredeep. Methods and methodology - generalization of data on the lithology of Devonian deposits, analysis of materials on the development of paragenic facies associations in evaporite basins, construction of a principled model of the hydrodynamics of the Dobrudja basin on this basis and predicting the distribution of various lithogenetic types in the Devonian period. Historical-catagenetic reconstructions were carried out on the basis of the provisions of the fluid-dynamic concept of catagenesis. Results. On the basis of the reconstruction of the dynamics of the sea basin and the nature of the lithofacies zonation, the conditions of Middle-Late Devonian sedimentation were modeled. A wider development of sediments enriched in organic matter, both in the section and laterally, is argued. First of all, this applies to the Middle Devonian deposits, which, together with the Lower Devonian black shale formations, formed the body of oil and gas formation centers, that were localized in the depocenters of the Tuzliv and Alibey depressions. The Devonian sediments were affected by two major cycles of catagenesis, with active substages (so-called critical moments) associated with large-scale fluid migration. The time of manifestation of the active substage of the first cycle (Middle-Late Carboniferous) was the main one in the migration of hydrocarbons, which is associated with a sufficiently high degree of post-diagenesis of the generating strata: gradation of catagenesis MK5 (Lower Devonian), MK3 - MK4 (Eifelian). Hydrocarbons moved through the zones of regional decompaction, which were developed at three hypsometric levels. In this case, flows of hydrocarbons of different phase composition were formed. The source of the gas was the Lower Devonian deposits, and the main volume of oil was generated in the Eifelian layers. During the second cycle of catagenesis, due to a decrease in reservoir temperatures and a significant depletion of the potential of organic matter, only processes of reformation of previously formed hydrocarbon deposits are predicted. Due to the fact that the generation centers were confined to deposits of different ages, differed in temperature regime, ways of fluid migration, and were separated from each other, there are reasons to assume the existence of three oil and gas systems. Scientific novelty and practical significance. For the first time, a wider spatial and age range of development of oil and gas source strata, localized centers of generation, discrete paths and time of large-scale migration of hydrocarbons have been scientifically substantiated. The studies carried out provide good grounds for predicting the possibility of the formation of large volumes of hydrocarbons that could be accumulated in the Devonian deposits of the Dobrudja Foredeep.